Instilling the Values of Islamic Character in Early Childhood Through the Story of The Prophets / Menanamkan Nilai – Nilai Karakter Islami pada Anak Usia Dini Melalui Kisah Para Nabi - Nur Anida Agustin Hayati (STAI Ma'had Aly Al-Hikam Malang, 2020)
Cultivating character values in early childhood is very important. This will be the basis for future children's character orders. The inculcation of Islamic character values is not only done through theory, but also requires practical control. The method used to instill Islamic character values is telling stories. The storytelling method is a method that tells orally about the history of Islam, the story of prophets, messengers, and friends. The purpose of applying this storytelling method is to introduce, immerse, and make eating habits based on religious and moral characteristics. This research is a literature review, where researchers collect primary and secondary data in the form of journals which are then analyzed. The results showed that the storytelling method for instilling character values in early childhood is the right method. Because with the storytelling method children are more interested, can learn various Islamic characters such as being honest, creative, peace-loving, sincere, patient, independent, getting to know their God better, and knowing the obligations they have to do. The teacher's role to develop in storytelling is to become a leader, more inviting, facilitating, guiding, teaching, being a motivator for early childhood to understand good and bad morally and see the content of religious teachings on children's growth and faith.